(untitled) - Karp, Susan (New York, 1998)
Mutual funds are good for those who want to take part in the current stock-market boom but have neither the time nor inclination to pick individual stocks on their own. But with nearly 9,000 mutual funds on the market, which ones should you pick or avoid? If you're faced with this dilemma, turn to Susan Karp's Smart Guide to Profiting from Mutual Funds. Karp, a finance journalist, writes a broad introduction to the world of mutual funds, and covers everything from the different types of stock funds available (e.g., aggressive, growth, index, sector, bond, and money funds) to assessing your own goals and objectives as well as tolerance for risk. While Karp does not recommend individual funds, she goes into detail on how to evaluate and buy them and what performance indicators are most important. In addition, the book is sprinkled with phone numbers and URLs of various fund companies and other resources that can help you evaluate different funds. --Harry C. Edwards
Keywords: Mutual funds; United States